POLICY OF PATIENT SAFETY GOVERNANCE FOR HOSPITALIZED PATIENT AT THE KOJA PUBLIC HOSPITAL IN 2019 - Yolanda, Tiara Fani; Basabih, Masyitoh (UI Scholars Hub, 2020)
Clinical governance is a structured organizational framework to improve the quality and safety of patients in the hospital which made by the NHS into seven pillars and adjusted to RI Law No. 44 of 2009. The evaluation results from the quality and patient safety team of Koja Public Regional Hospital in 2018, showed that there is Fall Patient incidents (6 events), KTD and KNC (13 events) which is not following the 0 % of the target from Patient Safety Goals by the Ministry of Health. The study was conducted to analyze patient safety governance for hospitalized patients at the Koja Public Regional Hospital in 2019 based on 4 of the Clinical Governance theories, which are clinical leadership, clinical audit, clinical effectiveness (guidelines); and education, training, and development of conservation profession. This study is using in-depth interview methods through the Purposive Sampling method and also reviewing documents conducted from May to June 2019. The results of the study found that the implementation of Clinical Leadership in Koja Public Hospital was running quite well but not yet optimal because the leadership system, which used the Line Organization to help to faster the decision-making process, is still weak in monitoring. From the Clinical Pathway (CP) evaluation, The medical audit was done well, but the monitoring and evaluation aspects are not yet optimal. The evaluation of clinical effectiveness showed that the compliance to fill the CP form was not optimal because of the lack of CP benefit socialization. Training and courses were done pretty well but have not been evaluated yet. The management team recommends monitoring, collaborating with the medical committee to evaluate the CP usage, providing training related to CP procurement to increase understanding, and also providing necessary training and its evaluation